2020
DOI: 10.1016/j.celrep.2020.107841
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Control of Super-Mendelian Inheritance in Gene Drives

Abstract: SUMMARY Synthetic CRISPR-based gene-drive systems have tremendous potential in public health and agriculture, such as for fighting vector-borne diseases or suppressing crop pest populations. These elements can rapidly spread in a population by breaching the inheritance limit of 50% dictated by Mendel’s law of gene segregation, making them a promising tool for population engineering. However, current technologies lack control over their propagation capacity, and there are important concerns about pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 37 publications
(53 reference statements)
5
40
0
Order By: Relevance
“…Briefly, we fused Escherichia coli dihydrofolate reductase domains to SpCas9 to promote its rapid proteasomal degradation in the absence of the stabilizing small molecule trimethoprim (TMP) 31,32 . We showed that TMP addition to the fruit fly diet stabilized our modified SpCas9 (DD2-Cas9) and sustained super-Mendelian inheritance control of a CopyCat active genetic element 30 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Briefly, we fused Escherichia coli dihydrofolate reductase domains to SpCas9 to promote its rapid proteasomal degradation in the absence of the stabilizing small molecule trimethoprim (TMP) 31,32 . We showed that TMP addition to the fruit fly diet stabilized our modified SpCas9 (DD2-Cas9) and sustained super-Mendelian inheritance control of a CopyCat active genetic element 30 .…”
Section: Resultsmentioning
confidence: 96%
“…This is an important question since, to our knowledge, no published genedrive work has thus far been able to precisely establish the timing of drive conversion events. We recently developed a small-molecule-controlled system for use in active genetics approaches including CRISPR-based genedrive systems 30 . Briefly, we fused Escherichia coli dihydrofolate reductase domains to SpCas9 to promote its rapid proteasomal degradation in the absence of the stabilizing small molecule trimethoprim (TMP) 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…To test the transgenesis efficiency of these constructs, we injected each plasmid into a Drosophila vasa -Cas9 line, expressing Cas9 in the germline (Fig. 4b ) 43 , 44 . In each case, the injected G0 adults were single-pair crossed to w−/w− mutant flies, and the presence of the GFP marker in the resulting G1 offspring indicated successful transgene integration.…”
Section: Resultsmentioning
confidence: 99%
“…Since we observed improved activity when using scaffold variants in both Culex quinquefasciatus and Drosophila melanogaster , we wondered whether these variants could be effectively used in a gene drive strategy, and whether they would improve efficiency in these genetic systems. To test these hypotheses, we employed a split-gene drive strategy (aka CopyCat) in Drosophila 19 , 43 , 45 , 46 . Briefly, a CopyCat element consists of a transgene containing a gRNA element (and a GFP marker) flanked by two HAs, which match the targeted locus sequence on each side of a cut site generated by the gRNA within the transgene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach might be to use a promoter that drives strong expression with less temporal specificity and to chemically control the timing of Cas9 activity (e.g. with tamoxifen or trimethoprim [42]). Both wild release applications to constitute a ‘gene drive’ and laboratory applications to facilitate breeding complex genotypes will benefit from further increasing the efficiency of genotype conversion by improved genetic strategies.…”
Section: Discussionmentioning
confidence: 99%